2000
DOI: 10.1104/pp.124.2.865
|View full text |Cite
|
Sign up to set email alerts
|

Gene Induction of Stilbene Biosynthesis in Scots Pine in Response to Ozone Treatment, Wounding, and Fungal Infection

Abstract: The S-adenosyl-l-methionine:pinosylvin-O-methyltransferase (PMT) 2 gene was sequenced from Scots pine (Pinus sylvestris). The open reading frame is arranged in two exons spaced by one 102-bp intron. Promoter regulatory elements such as two "CAAT" boxes and one "TATA" box were identified. Several cis-regulatory elements were recognized: stress-responsive elements (Myb-responsive elements) as well as G, H, and GC boxes. Moreover, elicitor-responsive elements (W boxes) and a sequence resembling the simian virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 36 publications
1
56
1
3
Order By: Relevance
“…PAL and STS were also induced in mock-infected discs, presumably as a result of the wounding response following disc cutting. Indeed, wound induction of PAL and STS gene expression has been shown to occur in different plant species (Lawton and Lamb, 1987;Chiron et al, 2000b). Like PAL and STS, ROMT gene expression was induced in P. viticola-infected and UV-and AlCl 3 -treated leaf discs, reaching a maximum 24 h posttreatment.…”
Section: Analysis Of Romt Gene Expressionmentioning
confidence: 98%
See 1 more Smart Citation
“…PAL and STS were also induced in mock-infected discs, presumably as a result of the wounding response following disc cutting. Indeed, wound induction of PAL and STS gene expression has been shown to occur in different plant species (Lawton and Lamb, 1987;Chiron et al, 2000b). Like PAL and STS, ROMT gene expression was induced in P. viticola-infected and UV-and AlCl 3 -treated leaf discs, reaching a maximum 24 h posttreatment.…”
Section: Analysis Of Romt Gene Expressionmentioning
confidence: 98%
“…In Scots pine, PMT gene transcription was shown to be induced by various stresses, including ozone treatment, fungal infection, and wounding (Chiron et al, 2000b). Semiquantitative RT-PCR analysis of ROMT expression showed that, like PAL and STS genes, ROMT expression was induced in P. viticola-infected and in UV-and AlCl 3 -treated leaf discs.…”
Section: Romt Gene Expression Is Induced By Biotic and Abiotic Stressesmentioning
confidence: 99%
“…Bavaresco et al (1997) found that mechanical damage of grapevine berry skin led to the synthesis of low stilbene levels in uninfected berries. Chiron et al (2000b) and Chung et al (2001) revealed that wounding caused by a mock fungal inoculation or leaf punching resulted in the induction of the stilbene biosynthesis genes in Scots pine (STS, PMT) and peanut (STS), respectively. Rudolf and Resurreccion (2005) found that slicing of peanut kernels increased production of t-resveratrol.…”
Section: Biotic and Abiotic Stresses As Regulators Of Stilbene Biosynmentioning
confidence: 99%
“…However, a study by Pearce (1996) showed that the levels of the stilbene glucosides astringin and isorhapontin, the main constitutive antifungal stilbenic compounds in the Picea bark, were not altered by ozone application in the stem tissues of Sitka spruce (Picea sitchensis). Subsequently, several investigations revealed that ozone fumigation enhanced the transcript levels of STS and PMT genes in Scots pine (Zinser et al 1998;Chiron et al 2000b). Schubert et al (1997) revealed that Vst1, an STS gene from grapevine, was transcriptionally regulated by ozone application, and the Vst1 promoter sequences, essential for the ozone-induced expression, have been identified.…”
Section: Biotic and Abiotic Stresses As Regulators Of Stilbene Biosynmentioning
confidence: 99%
“…2005;Kodart et al. 2002: Chiron et al, 2000. Both compounds demonstrated aniifungal and antibacterial activities (Lindberg et al, 2004;Seppanen et al, 2004: Celimene et ni., 1999.…”
Section: Introductionmentioning
confidence: 98%